Alien earths: the new science of planet hunting in the cosmos - Kaltenegger, Lisa. (New York: St. Martin's Press, 2024)
c
Introduction : a message from our pale blue dot -- At the brink of finding life in this cosmos -- How to build a habitable world -- What is life? -- How to search for life in the cosmos -- Worlds that shook science -- No place like home -- At the edge of cosmic knowledge -- Epilogue : spaceship Earth.
Includes index.
Keywords: Extrasolar planets; Life on other planets